Single-cell RNA-seq reveals developmental deficiencies in both the placentation and the decidualization in women with late-onset preeclampsia - Yang, Jing; Gong, Lili; Liu, Qiming; Zhao, Huanqiang; Wang, Zekun; Li, Xiaotian; Tian, Weidong; Zhou, Qiongjie (Frontiers in Immunology, 2023)
Preeclampsia (PE) is a leading cause of morbidity and mortality in both pregnant women and fetuses. Increasing lines of evidence have suggested that both the placenta from the fetus and the decidua from the mother are involved in the pathogenesis of PE. However, the molecular mechanism of PE remains elusive partly because of the heterogeneity of both tissues. In this study, we performed single-cell RNA-sequencing on the placenta and the decidual from patients with late-onset PE (LOPE) and healthy pregnant women. Single-cell transcriptome analyses revealed significant alterations of key biological processes in the placenta and the decidua of patients with LOPE, indicating function impairment in the placentation and decidualization. These findings provide new perspectives on the molecular mechanisms underlying the roles of the placenta and the decidua in the pathogenesis of PE.